Administration of a vaccine composed of dendritic cells pulsed with premalignant oral lesion lysate to mice bearing carcinogen-induced premalignant oral lesions stimulates a protective immune response - De Costa, Anna-Maria A. (2012)
The use of dendritic cell (DC) vaccines as treatment for malignancy is complicated by immune evasion tactics often employed by carcinomas such as head and neck squamous cell carcinoma (HNSCC). The present study aims to determine if an immune response can be elicited by administering a DC vaccine during the premalignant stages of HNSCC, prior to development of immune escape. Mice treated with the carcinogen 4-nitroquinoline 1-oxide (4NQO) in drinking water develop premalignant oral lesions that progress to HNSCC. As previous studies demonstrated that premalignant lesions and HNSCC overexpress common tumor antigens, bone marrow-derived DCs were pulsed with premalignant lesion lysate (DCpm) and administered to 4NQO-treated mice exhibiting premalignant lesions. Lesion progression was tracked through endoscopy, which revealed that DCpm vaccination and control vaccination with dendritic cells pulsed with normal tongue epithelium lysate (DCnt) significantly decreased lesion burden at 8 weeks. Analysis of lymph node cells revealed that while DCnt vaccination resulted in a rapid increase in total lymphocyte count, levels of activated conventional CD4(+) T cells and Th1, Tc1, Th17, Tc17, and Th2 cells, DCpm vaccination results in a delayed, yet substantial, increase in these immune effector mechanisms. This suggests that dendritic cell vaccination may have a beneficial effect on clinical outcome regardless of type of antigenic stimulation. Also, pulsing DCs with premalignant lysate rather than normal tongue epithelium lysate affects the dendritic cells in a way that delays the immune effector response upon vaccination of premalignant lesion-bearing mice.